Fit for purpose? Introducing a rational priority setting approach into a community care setting. Issue 4 (20th June 2016) - Cornelissen, Evelyn; Mitton, Craig; Davidson, Alan; Reid, Colin; Hole, Rachelle; Visockas, Anne-Marie; Smith, Neale
Abstract : Purpose: – Program budgeting and marginal analysis (PBMA) is a priority setting approach that assists decision makers with allocating resources. Previous PBMA work establishes its efficacy and indicates that contextual factors complicate priority setting, which can hamper PBMA effectiveness. The purpose of this paper is to gain qualitative insight into PBMA effectiveness. Design/methodology/approach: – A Canadian case study of PBMA implementation. Data consist of decision-maker interviews pre ( n =20), post year-1 ( n =12) and post year-2 ( n =9) of PBMA to examine perceptions of baseline priority setting practice vis-à-vis desired practice, and perceptions of PBMA usability and acceptability. Findings: – Fit emerged as a key theme in determining PBMA effectiveness. Fit herein refers to being of suitable quality and form to meet the intended purposes and needs of the end-users, and includes desirability, acceptability, and usability dimensions. Results confirm decision-maker desire for rational approaches like PBMA. However, most participants indicated that the timing of the exercise and the form in which PBMA was applied were not well-suited for this case study. Participant acceptance of and buy-in to PBMA changed during the study: a leadership change, limited organizational commitment, and concerns with organizational capacity were key barriers to PBMA adoption and thereby effectiveness. Practical implications: – These findings suggest that a potential way-forward includes adding a contextual readiness/capacity assessment stage to PBMA, recognizing organizational complexity, and considering incremental adoption of PBMA's approach. Originality/value: – These insights help us to better understand and work with priority setting conditions to advance evidence-informed decision making.